Empowering Roti Mashita MSMEs in Bogor: Optimizing Digital Marketing and Business Management Based on SWOT Analysis - Heirunissa; Jhonson Sitanggang; Wahjuny Djamaa; Rio Eldianson; Muhammad Andriansyah; Prastianti (Edumedia Solution, 2026)
The Roti Mashita MSME in Bogor has great potential with good product quality and affordable prices, but faces obstacles in digital marketing and simple business management aspects amidst the tight competition of modern bakeries. This community service activity aims to formulate an appropriate business development strategy for the Roti Mashita MSME through a SWOT analysis approach. The method used is descriptive qualitative with data collection through observation, in-depth interviews, and SWOT matrix analysis (Strengths, Weaknesses, Opportunities, Threats). The analysis results show that Roti Mashita MSME is in a strong position in terms of product quality (S), but weak in digital presence (W). There is a significant opportunity in the trend of delivery services in Bogor (O), although the threat of rising raw material prices still looms (T). The formulated strategies include accelerating digital marketing, registering on food delivery platforms, and improving simple financial management. Through a SWOT matrix analysis based on the results of S-O (Strength-Opportunities), W-O (Weaknesses-Opportunities), S-T (Strength-Threat) and W-T (Weaknesses-Threat), the results show that the Bogor market has great potential for unyil bread products due to the diverse character of consumers and high tourism activities. The implementation of a SWOT-based strategy is expected to increase the competitiveness and market reach of Roti Mashita MSMEs in a sustainable manner.